Social Inequalities and International Trade: A Cross-Country Perspective - Cieślik, Andrzej; Michałek, Jan Jakub; Mycielski, Jerzy (Journal of Income Distribution®, 2014)
In this article we study the role of social inequalities in international trade using the theory consistent gravity model. In addition to the standard set of gravity variables we use aggregate social development indicators such as Human Development Indices (HDI), Human Poverty Index (HPI), Gender Development Index (GDI), as well as detailed measures reflecting various forms of social inequalities. Our results show that measures of social inequalities significantly affect the volume of international trade flows.